Collagen extraction and purification for scaffold 3D printing using hyaluronic acid and chemical crosslinking - Fernández, Pablo Andrés (2023)
Biodegradable scaffolds with three-dimensional porous structure are fundamental components for tissue engineering. Collagen is the main protein of the human extracellular matrix, its structure allows the union, migration and in several cases the differentiation of the cells. However, its use has been limited due to low processability by the means of layer-by-layer technologies. In the present, a simple and economical method is developed for collagen purification from porcine skin using treatments with acidic and salt solutions. This preserves the structure of the fibers unlike normally used enzymatic procedures which denature the protein. A collagen ink was prepared with collagen and hyaluronic acid, which can be homogenously extruded through the bioprinter needle, presenting appropriated viscosity and stability for printing 3D scaffolds. Finally, these structures were lyophilized and crosslinked chemically to improve their physical-chemical properties.